Room‐Temperature Exciton‐Based Optoelectronic Switch. Issue 5 (12th January 2021) - Ye, Tong; Zhou, Boxuan; Liu, Zeyi; Li, Yongzhuo; Shen, Hongzhi; Ning, Cun‐Zheng; Li, Dehui
Abstract: Excitons, bound pairs of electrons and holes, could act as an intermediary between electronic signal processing and optical transmission, thus speeding up the interconnection of photoelectric communication. However, up to date, exciton‐based logic devices such as switches that work at room temperature are still lacking. This work presents a prototype of a room‐temperature optoelectronic switch based on excitons in WSe2 monolayer. The emission intensity of WSe2 stacked on Au and SiO2 substrates exhibits completely opposite behaviors upon applying gate voltages. Such observation can be ascribed to different doping behaviors of WSe2 caused by charge‐transfer and chemical‐doping effect at WSe2 /Au and WSe2 /SiO2 interfaces, respectively, together with the charge‐drift effect. These interesting features can be utilized for optoelectronic switching, confirmed by the cyclic PL switching test for a long time exceeding 4000 s. This study offers a universal and reliable approach for the fabrication of exciton‐based optoelectronic switches, which would be essential in integrated nanophotonics. Abstract : This work presents a room‐temperature exciton‐based optoelectronic switch in WSe2 monolayer. The emission intensity of WSe2 /Au and WSe2 /SiO2 exhibits opposite behaviors upon voltage biasing, because of different dopings of WSe2 caused by charge‐transfer and chemical‐doping effect at WSe2 /Au and WSe2 /SiO2 interfaces, respectively. This study offers a universal and reliable approach to construct exciton‐based optoelectronic switch for integrated nanophotonics.